CIPP Evaluation Model In The Yellow Book Reading Acceleration Program PP. Al Akhyariyah Blega Bangkalan - Isrok, Isrok; Mutiara Sari Dewi (al-Afkar, Journal For Islamic Studies, 2025)
The Yellow Book Reading Acceleration Program at PP Al Akhyariyah Blega Bangkalan differs from similar programs in Indonesian Islamic boarding schools. This program requires students to fully read and understand the book over a structured timeline divided into three stages: 1) one year to master nahwu sorrof, 2) one year to study the book content, and 3) three years to fully comprehend the *Fathul Qorib* Yellow Book. Graduation each year is mandatory for students who meet the criteria. This study uses the CIPP evaluation model to assess the program. The results show: 1) Context evaluation indicates the program was developed with consideration of local regulations, including the Decree of the Roudlotul Al Akhyariyah As Syafi Foundation; 2) Input evaluation highlights that the curriculum, infrastructure, and supporting tools were appropriately designed by the boarding school; 3) Process evaluation confirms students were informed about memorization and comprehension targets at the start of the program; 4) Product evaluation finds that while the program has been implemented effectively, full success has not yet been achieved, as the quality of students’ reading and understanding of Fathul Qorib requires improvement, especially in accuracy of nahwu sorrof and grammar. The acceleration program is crucial for enhancing students’ personal and social quality, promoting Islamic syi’ar, and instilling moral values and character through habituation in reading the Yellow Book.